Youth suicide in the school context. (May 2022) - Poland, Scott; Ferguson, Sara
Abstract: Across the domains of youth risk behavior, suicidality is a significant concern for parents and professionals alike, requiring ongoing efforts to better understand and prevent rising trends. Recent examinations of suicidal behaviors in the United States over the last decade revealed an increase in emergency and inpatient hospital settings. Of importance, seasonal variations were demonstrated, finding the lowest frequency of suicidality encounters in summer months, and observed peaks in the fall and spring, during the school year. Given these findings and the fact that youth spend nearly half of their time at school, consideration of youth suicide in the school environment is critical. This paper will review the trends of youth suicide within the school context, exploring factors such as at-risk youth, bullying, relevant legal issues, and the current state of crisis response in school settings. Recommendations for prevention, intervention, and postvention will be provided. The authors propose that school professionals play a vital role in addressing youth suicide and will aim to provide guidance on effective crisis response within the school context. Highlights: Recent research supports the growing rates of youth suicidality and the school context is an ideal setting for prevention. Variety of prevention programming available, requiring additional research and replication. Prevention, intervention, and postvention efforts are imperative and are implemented variably across school districts. School professionals are an integral part of the prevention of and crisis response to youth suicide.